The role of inflammasomes in cutaneous pathology - Ciążyńska, Magdalena; Narbutt, Joanna; Skibińska, Małgorzata; Lesiak, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Inflammasomes are large intracellular multiprotein complexes, which constitute a novel part of the innate immune system. In response to danger signals from pathogens or other harmful agents, inflammasomes assemble resulting in production of the inflammatory cytokines. We discuss recent knowledge of the role of deregulated inflammasome activity in skin pathologies such as autoinflammatory diseases as well as common skin diseases such as psoriasis and atopic dermatitis. We also present an insight into the activation and effector mechanisms of inflammasomes in skin carcinogenesis. The complex influence of inflammasome on cutaneous disorders raises new challenges and opportunities for the treatment of skin diseases.